Implementation of Kirkpatrick evaluation model in Building Information Modeling (BIM) training program - M. Agphin Ramadhan; Ririt Aprilin Sumarsono; Arini Anindya Achmad; Abdramane Cisse (Faculty of Engineering, Universitas Negeri Yogyakarta, 2022)
This research aims to evaluate BIM WIKA Intermediate Allplan training, especially batch 8. The evaluation guide used refers to Kirkpatrick's evaluation model which is limited to levels 1 and 2. This research uses evaluation research methods with a quantitative approach. The respondents in this study were all participants who had participated in the BIM WIKA Intermediate Allplan Batch 8 training series from beginning to the end. The data was collected using questionnaires and testing instruments. The data obtained was analyzed using a weighting formula from Kirkpatrick to determine participant’s reaction to the training program, as well as improvement and achievement of participant’s learning outcomes during training activities. The result of participant’s reaction evaluation to implementation of BIM WIKA Allplan Intermediate Training Program in batch 8 raised a high positive reaction from trainees. Where’s the highest satisfaction’s level is training material component by 89%, and the lowest satisfaction’s level is learning media component by 80%. Meanwhile, in learning evaluation, it was found that the training can increase BIM knowledge for most of trainees, and they were able to practice the knowledge gained during training by conducting practical tests well.